Espacialização da precipitação pluviométrica trimestral e anual da sub-bacia 17 - MARCUZZO, Francisco Fernando Noronha (2017)
The basin of the Amazon River is the world's largest water availability and extension. This region, as well as other river regions of Brazil, is subdivided into ten sub-basins, which are identified by codes 10-19, and the sub-basin analyzed in this study in question is the sub-basin 17. The statement of the spatial rainfall dissemination, medium or long periods, highlights the constancies of rhythm climate of an area, enabling find other areas wetter and drier, and the evolution regions on time. This study is meant to examine the quarterly seasonal variations and total annual rainfall in the sub-basin 17 (direct tributary of the Amazon river basin), identifying areas of higher quarterly and annual precipitation. The area of the sub-basin 17 municipalities full or in part into four units of the Brazilian federation: Amazonas, Mato Grosso, Para and Rondonia and two administrative regions: North and Midwest. For the first quarter, the wetter the sub-basin 17, the highest rainfall was observed in the central region, registering volume of rainfall of 1,000mm. Already the Northeast part of the sub-basin 17 recorded minimum of 650mm in the first quarter. It is noted in general that there was a reversal from north to south and vice versa, from one quarter to another quarter, as the region with more and less rainfall in the sub-basin 17. Area Tapajós River andTeles Pires River.